Incidence and types of congenital heart disease at a referral hospital in Jordan: retrospective study from a tertiary center - Hasan, Abeer A.; Abu Lehyah, Naser Aldain A.; Al Tarawneh, Moath K.; Abbad, Mahmoud Y.; Fraijat, Areen G.; Al-Jammal, Razan A.; Moamar, Dania M.; Shersheer, Qasem A.; Guthrie, Scott O.; Starnes, Joseph R. (Frontiers in Pediatrics, 2023)
Congenital heart disease (CHD) is the most common birth defect and accounts for significant global morbidity and mortality. Relatively little is known about the epidemiology of CHD in Jordan or the manner in which CHD is identified. Methods A retrospective medical record review was conducted for all neonates who had an abnormal echocardiogram performed at a tertiary referral hospital. All included neonates had echocardiography performed by the same pediatric cardiologist at the discretion of the treatment team. Descriptive statistics were used to describe CHD incidence, types of CHD identified, and mechanism of identification.The incidence of congenital heart disease was 17.8 per 1,000 live births. This rose to 24.6 per 1,000 if patent ductus arteriosus in preterm infants was included. The most common identified abnormalities were PDA, atrial septal defects, persistent pulmonary hypertension, septal hypertrophy, and ventricular septal defects. Most children were evaluated either for a murmur heard on exam or as a part of screening due to other comorbidities or risk factors. Less than 1% of children had a prenatal diagnosis. There was a higher rate of persistent pulmonary hypertension during the COVID-19 pandemic than before (p<0.001). Conclusions There is a high incidence of CHD in Jordan. Increased prenatal and perinatal screening for CHD may allow for earlier detection.